(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Previous work on routing in MANETs has resulted innumerous routing protocols that aim at satisfying constraints such asminimum hop or low energy. Existing routing protocols often fail todiscover stable routes between source and sink when route availabilityis transient, i.e., due to mobile devices switching their network cardsinto low-power sleep modes whenever no communication is takingplace. In this thesis, we introduce a new approach stability awaresource routing protocol that is capable of predicting the stability (i.e.,expiration time) of multiple routes. Proposed protocol selects the routethat minimizes hop count while staying available for the expectedduration of packet transmission. The stability aware routing (SAR)resolve the problem of SADSR protocol indicate a significant increasein route discovery success rate with comparable route establishmentand maintenance overheads.